Severe Renal Mass Reduction Impairs Recovery and Promotes Fibrosis after AKI - Polichnowski, Aaron J. (American Society of Nephrology, 2014)
Preexisting CKD may affect the severity of and/or recovery from AKI. We assessed the impact of prior graded normotensive renal mass reduction on ischemia-reperfusion–induced AKI. Rats underwent 40 minutes of ischemia 2 weeks after right uninephrectomy and surgical excision of both poles of the left kidney (75% reduction of renal mass), right uninephrectomy (50% reduction of renal mass), or sham reduction of renal mass. The severity of AKI was comparable among groups, which was reflected by similarly increased serum creatinine (S(Cr); approximately 4.5 mg/dl) at 2 days, tubule necrosis at 3 days, and vimentin-expressing regenerating tubules at 7 days postischemia-reperfusion. However, S(Cr) remained elevated compared with preischemia-reperfusion values, and more tubules failed to differentiate during late recovery 4 weeks after ischemia-reperfusion in rats with 75% renal mass reduction relative to other groups. Tubules that failed to differentiate continued to produce vimentin, exhibited vicarious proliferative signaling, and expressed less vascular endothelial growth factor but more profibrotic peptides. The disproportionate failure of regenerating tubules to redifferentiate in rats with 75% renal mass reduction associated with more severe capillary rarefaction and greater tubulointerstitial fibrosis. Furthermore, initially normotensive rats with 75% renal mass reduction developed hypertension and proteinuria, 2–4 weeks postischemia-reperfusion. In summary, severe (>50%) renal mass reduction disproportionately compromised tubule repair, diminished capillary density, and promoted fibrosis with hypertension after ischemia-reperfusion–induced AKI in rats, suggesting that accelerated declines of renal function may occur after AKI in patients with preexisting CKD.